Corruption and change: the impact of foreign direct investment - Robertson, Christopher J.; Watson, Andrew (Strategic Management Journal, 2004)
Abstract This study examines influences on the level of corruption in countries from a strategic perspective. Corruption is one of the country‐level influences on market entry, investment, and other decisions fundamental to strategic management at the international level. The study examines the impact on corruption of change in levels of foreign direct investment (FDI). It uses the Corruption Perceptions Index (CPI) scores computed by Transparency International for 1999 and 2000. Results indicate that the more rapid the rate of change in FDI, the higher the level of corruption. Higher levels of perceived corruption are associated with each of two dimensions of national culture: uncertainty avoidance and masculinity. Research and managerial implications are also discussed. Copyright © 2004 John Wiley & Sons, Ltd.